Gaussimeter with automatic movement for the evaluation of the density of the magnetic flow in permanent magnets - Gonzales-Balladares, Julio David (2024)
The 2022 quarantine period exposed the need to design laboratory instruments that were accessible to students, allowing them to conduct experiments from home. Although many magnetism studies have developed manually displaced gaussmeters, only a few of them have been automated. Therefore, this study presents the design of a gaussmeter made with construction toy parts and an Arduino UNO development board to quantify the magnetic flux density in permanent magnets. To evaluate its operation, precision and robustness tests were carried out. In this way, the Kruskal-Wallis test showed similarity in the experimental readings with the WSH315 sensor between 1.62–3.54 cm. Meanwhile, the Wilcoxon-Mann-Whitney test showed limitations in terms of accuracy. And the Youden-Steiner test showed robustness to polarity rotation in the magnet at a distance of 1.19 cm with the AD22151 sensor. Finally, the experimental results showed proximity to analytical and numerical methods. Additionally, the results demonstrated the versatility of the gaussimeter to adapt to another sensor (MLX90393). Therefore, this design can be used to perform magnetism experiments at low cost.